Mixed mode interface fracture toughness of a multi-directional composite – UD/woven pair. (December 2019) - Mega, Mor; Banks-Sills, Leslie
Graphical abstract: Highlights: Mixed mode fracture toughness test results for a specific composite interface. Development of the first term of the asymptotic solution for the interface and material studied. Extension of the displacement extrapolation method and M-integral. Results for mechanical and residual curing stress intensity factors are presented. A three-dimensional failure surface is proposed for the material system studied. Abstract: Twenty-seven mixed mode Brazilian disk specimens were tested to obtain the fracture toughness of a delamination between two fiber reinforced composite plies in a multi-directional laminate, manufactured by means of a wet-layup. Using finite element analyses and conservative integrals, mechanical and residual curing stress intensity factors were found and used to calculate the interface energy release rate and phase angles. Based on these results, a three-dimensional failure criterion is proposed to obtain a failure surface. This criterion may be used to predict failure of a structure containing this material and interface.